Overbreadth Revisited - Stewart, Hamish (McGill Law Journal, 2024)
The norm against overbreadth—a law should not be overbroad in relation to its own purposes—is well established as a principle of fundamental justice under section 7 of the Charter. But the Supreme Court of Canada’s case law contains two competing formulations of this norm. According to the strict version of the norm, a law is overbroad if it applies in even one (actual or hypothetical) case that is not directly necessary to the achievement of its purpose. According to the relaxed version of the norm, a law is overbroad only if it applies in cases beyond those that are reasonably neces-sary to its operation. The strict version of the norm is unworkable because it relies on two un-tenable assumptions: first, that a law is always an instrument for achieving a purpose that can be fully specified apart from the idea of legal order; second, that a law can be drafted and applied so that it never goes beyond that pur-pose. The result is that, on a proper application of the strict version of the norm, all laws are overbroad. The relaxed version of the norm shares the first assumption but not the second. With respect to those laws that are properly characterized as instrumental, it would be bet-ter to abandon the strict version of the norm and adopt the relaxed version